Proceedings of the ACM Symposium on Virtual Reality Software and Technology 2003
DOI: 10.1145/1008653.1008693
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of team work in distributed collaborative virtual environments

Abstract: We present a framework for the design and evaluation of distributed, collaborative 3D interaction focussing on projection based systems. We discuss the issues of collaborative 3D interaction using audio/video for face-to-face communication and the differences in using rear projection based Virtual Environments. Further, we explore how the use of video/audio, input device representations and other disturbance factors typical of projection-based virtual environments affect co-presence, coworking and co-knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 27 publications
1
16
0
4
Order By: Relevance
“…During our early test trials, voice was found to be important for the immersion between people, which is consistent with earlier findings [3], [5]. So voice communication between the physical and virtual participants was supported by hooking the conference room's microphone and speaker system to the NVE operator's laptop.…”
Section: Workhop Setup and Deploymentsupporting
confidence: 89%
See 1 more Smart Citation
“…During our early test trials, voice was found to be important for the immersion between people, which is consistent with earlier findings [3], [5]. So voice communication between the physical and virtual participants was supported by hooking the conference room's microphone and speaker system to the NVE operator's laptop.…”
Section: Workhop Setup and Deploymentsupporting
confidence: 89%
“…The tool, however, is experimental and not used for real venues. Later systems have reported collaborative applications in NVEs, called Collaborative Virtual Environments (CVEs) [3], [4]. CVEs, however, focus more on the co-creation, co-manipulation, or collaborative achievement aspects of online interactions, as opposed to high fidelity information exchange in conferencing.…”
Section: Introductionmentioning
confidence: 99%
“…A collaborative virtual environment's objective (CVE), according to Goebbels et al [7], is to provide a common virtual space between distributed teams where they can meet each other as if in a "face to face" situation, coexisting and cooperating with each other as they share and manipulate data in real time.…”
Section: Related Workmentioning
confidence: 99%
“…Collaborative Virtual Environments are a special case of Virtual Reality Environments, where the emphasis is to provide distributed teams with a common virtual space where they can meet as if face-to-face, coexist and collaborate while sharing and manipulating, in real-time, the virtual artifacts of interest [9]. They can be seen as the result of a convergence of research interests within the Virtual Reality (VR) and CSCW communities.…”
Section: Computer Supported Collaborative Virtual Environmentsmentioning
confidence: 99%